(untitled) (Zaporizhzhia Historical Review, 2021)
The author draws attention to the actuality of linguistic problem in the conditions of democratic transformations of multinational society. The example of French-Canadian Quebec during the division of the democratic multicultural Canadian society into the English - and French speaking parts of the country represents a model for the analysis of prospects of democracy development in Ukraine and for the solution of different conflict situations by means of well-weighed state ethno politics.